The Weight of the Bargain : Investigating Prosecutors’ Emotions in Plea Bargaining Interactions in a United States Criminal Court - Nordquist, Cecilia Y ; 0000-0001-9386-7188 (Studia Sociologica Upsaliensia, 2025)
The majority of cases in the US criminal courts are disposed of through plea bargaining, an agreement where the accused accepts an offer from the prosecutor in return for their guilty plea. While procedural law formalises the interaction taking place in trials and proceedings, plea bargaining builds on informal negotiations between the prosecutor and the defence. In sociology, negotiation is considered a central feature of social interaction, requiring participants to agree on how to define a situation and its associated rules of action. In this process, emotions are seen as guiding the participants interpretative practices. Still, socio-legal research on the emotional and interactional dynamics of the plea process is limited. Drawing on ethnographic material from a US criminal state court, this dissertation explores the interactional dynamics of plea bargaining by zooming in on the role emotions play in prosecutors’ interpretations when forming plea offers and navigating plea negotiations. By focusing on the epistemic emotions of interest, doubt, certainty and uncertainty, I found these emotions to aid the prosecutors in processing large amounts of material while narrowing their scope of inquiry to enable quick decisions; ultimately informing their defining activities across cases. Moral emotions, instead, motivated the prosecutors’ actions and convictions in individual cases; incorporating varying emphasis on procedural correctness and/or a just resolution. In negotiation, trust was considered vital to reach a preferred outcome; with defence lawyers, trust expanded prosecutorial discretion, with victims, trust safeguarded the prosecutors’ bargaining power. In agreement with previous research, the prosecutors in this study rarely questioned the defendants’ guilt when forming a plea offer, yet the analysis showed how their offers often changed in interaction to secure a resolution to their cases, in effect dispersing prosecutorial power to a greater degree than previously asserted. Changes to the prosecutors’ offer resulted in justifications of their decisions by referencing the greater good of the community; the victim’s circumstances; or the organisational need to settle cases. This study develops our understanding of how prosecutors form their offers on a case-by-case basis by accounting for the role of emotions in preparation for and during front-line negotiation.